Spatial function analysis of students' learning pattern, learning posture and learning activities in school resource centers / Hani Farhana Mat Hasni, Azizah Md Ajis and Siti Norsazlina Haron - Mat Hasni, Hani Farhana; Md Ajis, Azizah; Haron, Siti Norsazlina (2021)
Aesthetic factors often become a consideration when associated with designing School Resource Center (SRC). This can be seen everywhere in SRCs around Malaysia. In fact, SRC is supposed to have a proper spatial planning that aligns with students' learning behavior, pattern and activities in order to sustain the utilization of the space, practical and functional to the user. Many assumed that activities occurred should adapt with the space provided, but in the case of SRC, it should be the other way round. Therefore, this paper intends to investigate the types of learning pattern, learning posture and activities in current situations in SRCs in Malaysia in order to create a proper space planning that could aid learning behavior. This paper provides an insight for future researchers interested in the area of sustainable space planning.